Analisis Implementasi Peraturan Gubernur DKI Jakarta Nomor 207 Tahun 2016 (Studi Kasus Tentang Penertiban Pemakaian/Penguasaan Tanah Tanpa Izin Yang Berhak Di Jakarta Timur) - Abdi Manap; Dony Hendartho (Jurnal Ilmu Administrasi Publik, 2023)
The phenomenon in this study is about the Analysis of the Implementation of the Governor of DKI Jakarta Regulation Number 207 of 2016 (Case Study on Controlling the Use/Control of Land Without Entitled Permits in East Jakarta East. The purpose of this study is to analyze the Analysis of the Implementation of the Governor of DKI Jakarta Regulation Number 207 of 2016 (Case Study on Controlling the Use/Control of Land Without Entitled Permits in East Jakarta East, to analyze what factors are the obstacles to the implementation of the DKI Jakarta Governor Regulation Number 207 of 2016 Concerning Control of Land Use/Control without Entitled Permit in East Jakarta Administrative City. To analyze what efforts are being made by the leadership to overcome these obstacle factors. This study uses a descriptive type of research with a qualitative approach, namely interviews, observations and documentation as well as informants consisting of the Civil Service Police Unit of the City of Adm Jakarta, Suban Assets of the City of Adm. East Jakarta. The results of this study are the implementation of the DKI Jakarta Governor's Regulation No. 207 of 2016 concerning Controlling the Use/Control of Land Without Permits has been carried out well even though there are still obstacles faced in the implementation of the control. The suggestion is to carry out regular socialization so that people comply and understand the importance of timely tax reporting and improve human resources by participating in activities regarding the Implementation of DKI Jakarta Governor Regulation Number 207 of 2016.